2015
DOI: 10.1002/psc.2739
|View full text |Cite
|
Sign up to set email alerts
|

A novel chimeric peptide with antimicrobial activity

Abstract: Beta-lactamase-mediated bacterial drug resistance exacerbates the prognosis of infectious diseases, which are sometimes treated with co-administration of beta-lactam type antibiotics and beta-lactamase inhibitors. Antimicrobial peptides are promising broad-spectrum alternatives to conventional antibiotics in this era of evolving bacterial resistance. Peptides based on the Ala46-Tyr51 beta-hairpin loop of beta-lactamase inhibitory protein (BLIP) have been previously shown to inhibit beta-lactamase. Here, our go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Using peptide conjugates for drug delivery into the cell has been a topic of interest and there are many anticancer [ 378 ], anti-inflammatory [ 379 ], and neurodegenerative [ 380 ] peptide conjugate drugs that are in clinical use or under investigation. Our group has also been focusing on combining the inhibitory properties of inhibitor peptides with CPPs [ 381 ]. Peptide vaccines (reviewed by Baig et al [ 382 ]) have also gained interest in the immunotherapy of different types of cancer [ 383 ] such as breast cancer [ 384 , 385 ] or lung cancer [ 386 ], virally mediated diseases such as influenza [ 387 ], Human papilloma virus (HPV) [ 388 , 389 ], and HIV, and neurodegenerative diseases [ 382 ] such as Alzheimer’s [ 390 ].…”
Section: Future Perspectives: Characterizing Membrane Active Peptmentioning
confidence: 99%
“…Using peptide conjugates for drug delivery into the cell has been a topic of interest and there are many anticancer [ 378 ], anti-inflammatory [ 379 ], and neurodegenerative [ 380 ] peptide conjugate drugs that are in clinical use or under investigation. Our group has also been focusing on combining the inhibitory properties of inhibitor peptides with CPPs [ 381 ]. Peptide vaccines (reviewed by Baig et al [ 382 ]) have also gained interest in the immunotherapy of different types of cancer [ 383 ] such as breast cancer [ 384 , 385 ] or lung cancer [ 386 ], virally mediated diseases such as influenza [ 387 ], Human papilloma virus (HPV) [ 388 , 389 ], and HIV, and neurodegenerative diseases [ 382 ] such as Alzheimer’s [ 390 ].…”
Section: Future Perspectives: Characterizing Membrane Active Peptmentioning
confidence: 99%
“…Unfortunately, many of the over 1300 different beta-lactamases can rapidly hydrolyze these inhibitors rendering them ineffective. In this context, continued search for novel inhibitors is an area of intense research 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that novel chimeric peptides, constructed by combining the N‐terminal residues of pVEC and beta‐lactamase inhibitory peptides, act as potential inhibitors that can move across the cell membrane . We also showed by SMD simulations that positively charged residues contribute to adsorption on the lipid bilayer via electrostatic interactions, while the N‐terminal truncated pVEC (del5 pVEC), I3A, L5A, R7A mutants, and scramble‐pVEC made weaker interactions with the lipids, highlighting the contribution of the N‐terminal residues and the relative position of the structural regions in the primary sequence to translocation .…”
Section: Introductionmentioning
confidence: 90%